Literasi Kesehatan dalam Pendidikan Islam: Studi Kasus Dampak Covid-19 bagi Mahasiswa UAD - Chairul Ashari Akhmad; Suyadi Suyadi (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2021)
Health literacy in islamic education: a case study affecting covid-19 for uad students. Health services, generally able to help make access to health inspection easier. But in this era health services brought about a renewal of a more modern service system. This is because it is not uncommon for people to experience difficulties that arise between students and the generalpublic. This is due to poor health literacy, especially in the midst of these expansions covid19. The care of the covid-19 patients requires support from their neighbors, families, and good health-care systems. When this is done to the maximum extent, it will be able to provide full positive energy for the sufferer. The health literacy research to be linked with islamic education in an effort to prevent the impact of covid-19 is to determine health literacy levels in people, especially students. The method adaptive in this assessment is a qualitative theoretical study that illustrates and summarizes the circumstances and situations of the covid-19 family literacy rate for uad students in islamic education. With quality health literacy make students more knowledgeable and skilled with reading or understanding, assessing and applying the accepted information to make decisions and to prevent viruses from forming and also in obtaining health